Pathology of intratracheal Mycoplasma mycoides subsp. capri infection in goats - KUMAR, HARENDRA; PARIHAR, N S; SINGH, K P (The Indian Journal of Animal Sciences, 2013)
Pleuropneumonia was produced by intratracheal inoculation of Mycoplasma mycoides subsp. capri in goats. The cardiac lobes were most frequently affected followed by apical and diaphragmatic lobes. Lungs were consolidated with thickened oedernatous pleura and interlobular septa; cut surfaces gave marbled appearance. Mediastinal lymphnodes were enlarged and congested. Microscopic lesions were of acute pleuropneumonia characterized by thickened pleura in continuation with interlobular septa, and infiltrated with neutrophils. Blood vessels and alveolar tissues were engorged. The consolidation was mostly due to the presence of neutrophilic aggregates in alveoli and bronchioles. The trachea revealed focal erosion and neutrophilic infiltration. Lymphnodes exhibited neutrophilic infiltration and vasculitis.